MORAL REASONING IN M.T. MISHBAH YAZDI’S THOUGHT: A CAUSAL TRANSCENDENTAL APPROACH TO FOSTERING ENVIRONMENTAL AWARENESS IN MUSLIM COMMUNITIES - Ahmad Sulaiman (ISSUE: Journal of Islamic Studies for Universal Dialogue, 2024)
Environmental problems continue to increase and reach serious levels and are unlikely to be reversed. This condition requires the participation of the entire community to collaborate in resolving the environmental crisis. Some scientists see that one of the obstacles to the green movement’s efforts is the failure of religious communities, including Muslims, to see environmental issues as important moral issues. This research offers Mishbah Yazdi’s thoughts regarding moral reasoning to overcome this problem. Mishbah Yazdi’s thinking includes understanding that the moral concept is something objective and can be grasped through human reasoning regarding the causal relationship between actions and the perfection of human existence. This view allows Muslims to see the importance of environmental issues as moral issues that are as important as other moral issues in religion. This ultimately has the potential to create a larger Islamic green moral movement that is needed to face the environmental crisis.